Visible-light-mediated eosin Y photoredox-catalyzed vicinal thioamination of alkynes: radical cascade annulation strategy for 2-substituted-3-sulfenylindoles - Tambe, Shrikant D.; Rohokale, Rajendra S.; Kshirsagar, Umesh A. (European Journal of Organic Chemistry, 2018)
An organic dye photoredox-catalyzed regiospecific radical cascade annulation strategy of 2-alkynyl-azidoarenes to generate 3-sulfenylindoles via vicinal thioamination of alkynes at room temperature, mediated by visible light, was developed. The method requires mild conditions, including visible light as a traceless green energy source, room temperature, eosin Y organic dye as a photoredox catalyst, ambient air as oxidant, and easily available starting materials to provide a green, efficient, metal- and strong-oxidant-free synthesis of 3-sulfenylindoles with broad substrate scope through vicinal thioamination of alkynes.